2012
DOI: 10.1002/aur.1260
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glutamate Concentration in the Auditory Cortex of Persons With Autism and First‐Degree Relatives: A 1H‐MRS Study

Abstract: Lay Abstract We investigated brain chemistry of the primary region of the brain involved in auditory processing in adults with autism spectrum disorder (ASD). Due to the highly heritable nature of ASD and the lack of prior brain chemistry data on unaffected first-degree relatives, we also enrolled parents of children with ASD (pASD), comparing both groups to a healthy adult control group. The technique used to quantify chemical signals was magnetic resonance spectroscopy (MRS), which we used to assess the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 68 publications
10
106
1
Order By: Relevance
“…MRS data from children cohorts indicate that autism groups exhibit reduced Glx levels in cortical gray matter (DeVito et al 2007), anterior cingulate cortex (Bernardi et al 2011), frontal and occipital cortex, and cerebellum (DeVito et al 2007). Recent research have suggested elevated Glx levels in ASD in the anterior cingulate cortex (Bejjani et al 2012) and putamen (Doyle-Thomas et al 2014) of children, and the auditory cortex of adults (Brown et al 2013). These results are consistent with the hyperglutamatergic theories of ASD, supporting an excitation/inhibition imbalance underlying the pathophysiology of ASD.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 76%
“…MRS data from children cohorts indicate that autism groups exhibit reduced Glx levels in cortical gray matter (DeVito et al 2007), anterior cingulate cortex (Bernardi et al 2011), frontal and occipital cortex, and cerebellum (DeVito et al 2007). Recent research have suggested elevated Glx levels in ASD in the anterior cingulate cortex (Bejjani et al 2012) and putamen (Doyle-Thomas et al 2014) of children, and the auditory cortex of adults (Brown et al 2013). These results are consistent with the hyperglutamatergic theories of ASD, supporting an excitation/inhibition imbalance underlying the pathophysiology of ASD.…”
Section: Magnetic Resonance Spectroscopysupporting
confidence: 76%
“…Glx levels were not significantly correlated with IQ or autism symptom measures. Several other groups have reported significantly increased glutamate concentration since then in regions including the anterior cingulate gyrus (Joshi:2012ir; Bejjani et al 2012) and auditory cortex (Brown et al 2013). Others have reported reduced Glx in autism or no group differences in similar regions of interest (DeVito et al 2007; Bernardi et al 2011; Horder et al 2013).…”
Section: In-vivo Evidence Of Increased Glutamate In Autismmentioning
confidence: 99%
“…In two studies reporting either negative effects or reductions in glutamate, subjects were sedated using drugs that are known to interact with GABA and glutamate transmission (DeVito et al 2007; Corrigan et al 2013), but such sedation is typically also used with lower functioning and/or younger children. Four studies to date have reported Glu levels separately or in addition to Glx (Harada et al 2010; Joshi et al 2012; Brown et al 2013; Hassan et al 2013). Of those, 3 reported increases in autism (Joshi et al 2012; Brown et al 2013; Hassan et al 2013) and one reported no significant differences (Harada et al 2010).…”
Section: In-vivo Evidence Of Increased Glutamate In Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamic acid decarboxylase (GAD) was reduced by 48%-61% in the parietal and cerebellar areas of the brains of people with autism compared with controls [84]. Increased glutamate concentration was demonstrated in the auditory cortex of persons with autism and first-degree relatives [85]. Proton magnetic resonance spectroscopy revealed lower Nacetylaspartate/creatine (NAA/Cr), γ-aminobutyric acid/creatine (GABA/Cr) and glutamate/creatine (Glx/Cr) in the frontal lobes of an autistic group compared with normal controls [86].…”
Section: Neurotransmitter Systemmentioning
confidence: 99%